The anhypostasis and enhypostasis : Barth's Christological method in view of Chalcedon - its nuance and complexity - Haley , James P (Stellenbosch Theological Journal, 2020)
Karl Barth departs from historical Protestant orthodoxy in his unique adoption of the dual formula anhypostasis and enhypostasis to explain the union of divine and human natures in the person of Jesus Christ. For Barth, these concepts help explain why the person of Jesus Christ must not be viewed statically in his being as the God-man, but dynamically in the event of God's movement of grace towards humanity. As such, Barth applies these concepts in his analysis of the Chalcedon definition of the Jesus Christ who exists as one person with two natures. In so doing, Barth further develops Chalcedon's definition of the two natures of Christ based upon the hypostatica unio. Not only must Chalcedon be interpreted through the revelation of God in Jesus Christ as event, but also event in the union of this human essence as the Son of Man as it participates in the divine essence. For Barth, the emphasis is not the combining of divine and human essence into one being, but that the eternal Christ has taken to himself human essence as the one Reconciler.